Exploring Strategies To Foster Cohesion And Coherence In Efl Writing: A Focus On Simple View Of Writing - Nora Fitria; Fauzi; Muchsin; Cut Muliana Zahra; Muhammad Usman; Bukhari Usman (Kodepena Indonesia, 2024)
EFL students often experience difficulties in writing coherent texts because of their limited understanding of English writing conventions. Many students have difficulty presenting and organizing ideas effectively, resulting in incoherent texts. These difficulties are also compounded by factors such as level of linguistic proficiency, learning methods, psychological factors, socio-cultural influences, and socio-political issues. This problem is likely widespread in EFL writing classes. The aim of this research is to explore strategies for fostering cohesion and coherence in EFL writing. The research method usesquantitative design with a survey approach.The population in this study was all students at school multiple linear regression, and t test for hypothesis testing. The research results show that the application of Simple View of Writing in EFL teaching significantly increases the cohesion and coherence of students' writing by focusing on comprehension and production of texts. This is important because coherence and cohesion ensure a clear flow in the writing, making it easier for readers to understand. Keywords: Cohesion, Coherence, EFL Writing, Simple View of Writing